Promosi kesehatan pada keluarga penderita dalam deteksi awal kekambuhan skizofrenia Pascapengobatan - Jaya Susanto, Yayi Suryo Prabandari, Sumarni (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Schizophrenia is a severe mental disorder that is expected could have a great relapse risk. Number of schizophrenic's patient in Bengkulu in the year of 2003 was 144 people. 42 people (29,17%)did not re-control post treatment in the mental hospital. The role of patient's family in early detection of schizophrenia patient's relapse is necessary for patient's recovery. Giving proportional information to the family effectiveness therefore is an effort that should be done. One of the way to give information is giving health education and distributing leaflet Objective: This research was aimed to find out the influence of mental health promotion by using group health education and distributing leaflet on knowledge and attitude of patient's family regarding early detection of schizophrenia patient's mental hospital in Bengkulu. Method: this study was a quasi experiment with nonrandomized pretest-postest kontrol group design. This research was done group health education and distributing leaflet regarding early detection of schizophrenia relapse in the group of schizophrenia patient's who did not re-kontrol. The data collected by questionnaire. Result: Group health education and distributing leaflet regarding early detection of schizophrenia patient's relapse have successful ion increasing the mean value of treatment group's knowledge and attitude. The difference value of attitude and knowledge during pretest, postest 1 and postest 2 were statistikally significant. Indeed there were differences on knowledge